MIGRATIONS AS A CAUSE OF GENETIC HOMOGENEITY IN PACIFIC HERRING (CLUPEA PALLASII) FROM THE SEA OF OKHOTSK - V. V. Gorbachev (Вавиловский журнал генетики и селекции)
Analysis of the molecular variability of mitochondrial DNA (mtDNA) control region sequences has shown no differentiation between samples of spawning herring from various parts of the Okhotsk Sea (p > 0,05). The lack of differentiation may be attributed to a constant gene flow between schools, while the proportion of migrants (Nm) can be calculated only indirectly. Global AMOVA for sample pairs or bulked samples shows that the intersample component comprises about 0,1–0,2 % of the total polymorphism (p > 0,1). This fact is considered to be a consequence of intense migration. The minimum portion of migrants for a locality per year varies within 3,6–9,5 %.